Strengthening Civil Rights Literacy among Indonesian Migrant Workers through Media-Based Legal Education during Integrated Itsbat Nikah Hearings in Sarawak - Yenny Aman Serah; Mella Ismelina Farma Rahayu; Syarifah Arabiyah; Aris Yulia; Adhytia Nugraha; Resmaya Agnesia Mutiara Sirait; Agustinus Astono (International Journal of Public Devotion, 2026)
Although integrated marriage validation (itsbat nikah) services are available to Indonesian migrant workers (PMI) in Sarawak, Malaysia, some participants still need information regarding court procedures, the function of marriage registration, family documents, and the protection of civil rights. This Community Service activity aims to strengthen PMI’s legal literacy through media-based legal education as a complement to the integrated marriage validation hearings at the Consulate General of the Republic of Indonesia (KJRI) in Kuching, with evaluation indicators including understanding of marriage validation procedures, perceptions of legal certainty, and the benefits of integrated services. The activity was conducted on December 4-8, 2025, by a collaborative Community Service (PKM) team from Panca Bhakti University in Pontianak, Tarumanagara University in Jakarta, and Sahid University in Jakarta, involving 102 Indonesian migrant worker couples. The activity employed an educational-participatory approach through observation, educational reporting, brief interviews, discussions, legal consultations, the distribution of brochures, and evaluation via questionnaires. The results of the activity showed that 77 applications for itsbat nikah (75.5%) were granted, 5 applications (4.9%) were rejected, and 20 applications (19.6%) were dismissed. As part of the PKM activities, a post-activity evaluation of 60 respondents showed that 87% fell into the “understand” and “fully understand” categories regarding the marriage validation procedure, 92% gave a positive assessment that marriage legalization provides legal certainty, and 93% assessed that the integrated service benefits families. The evaluation results indicate that media-based legal education can complement marriage registration services by providing more contextual and communicative information. This mentoring model can be developed as part of legal services for Indonesian migrant workers at Indonesian diplomatic missions abroad.Penguatan Literasi Hak Sipil Pekerja Migran Indonesia melalui Edukasi Hukum Berbasis Media pada Sidang Itsbat Nikah Terpadu di SarawakABSTRAKMeskipun layanan sidang itsbat nikah terpadu telah tersedia bagi Pekerja Migran Indonesia (PMI) di Sarawak, Malaysia, sebagian peserta masih memerlukan informasi mengenai prosedur persidangan, fungsi pencatatan perkawinan, dokumen keluarga, dan perlindungan hak sipil. Kegiatan Pengabdian kepada Masyarakat ini bertujuan memperkuat literasi hukum PMI melalui edukasi hukum berbasis media sebagai pendamping sidang itsbat nikah terpadu di Konsulat Jenderal Republik Indonesia (KJRI) Kuching, dengan indikator evaluasi meliputi pemahaman prosedur itsbat nikah, persepsi terhadap kepastian hukum, dan manfaat pelayanan terpadu. Kegiatan dilaksanakan pada 4-8 Desember 2025 oleh tim PKM kolaborasi dari Universitas Panca Bhakti Pontianak, Universitas Tarumanagara Jakarta, dan Universitas Sahid Jakarta dengan sasaran 102 pasangan PMI. Kegiatan menggunakan pendekatan edukatif-partisipatif melalui observasi, peliputan edukatif, wawancara singkat, diskusi, konsultasi hukum, pembagian brosur, dan evaluasi melalui angket. Hasil kegiatan menunjukkan bahwa 77 permohonan itsbat nikah (75,5%) dikabulkan, 5 permohonan (4,9%) ditolak, dan 20 permohonan (19,6%) dinyatakan gugur. Dalam rangkaian kegiatan PKM tersebut, evaluasi pascakegiatan terhadap 60 responden menunjukkan bahwa 87% berada pada kategori paham dan sangat paham terhadap prosedur itsbat nikah, 92% memberikan penilaian positif bahwa legalisasi perkawinan memberikan kepastian hukum, dan 93% menilai pelayanan terpadu memberikan manfaat bagi keluarga. Hasil evaluasi menunjukkan bahwa edukasi hukum berbasis media dapat melengkapi pelayanan itsbat nikah dengan penyampaian informasi yang lebih kontekstual dan komunikatif. Model pendampingan ini dapat dikembangkan sebagai bagian dari pelayanan hukum bagi PMI pada perwakilan Republik Indonesia di luar negeri.Kata Kunci :edukasi hukum berbasis media; itsbat nikah terpadu; literasi hukum PMI; pekerja migran Indonesia; pelayanan publik terpadu